2010
DOI: 10.1021/nl101052f
|View full text |Cite
|
Sign up to set email alerts
|

Probing Protein Kinase (CK2) and Alkaline Phosphatase with CdSe/ZnS Quantum Dots

Abstract: Semiconductor quantum dots (QDs) are used for the optical analysis of casein kinase (CK2) or the hydrolytic activity of alkaline phosphatase (ALP). Two schemes for the analysis of CK2 by a FRET-based mechanism are described. One approach involves the CK2-catalyzed phosphorylation of a serine-containing peptide (1), linked to CdSe/ZnS QDs, with Atto-590-functionalized ATP. The second analytical method involves the specific association of the Atto-590-functionalized antibody to the phosphorylated product. The hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
166
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 232 publications
(169 citation statements)
references
References 34 publications
2
166
0
1
Order By: Relevance
“…9A). 11 In addition to sensing configurations that use hole accepting metal complexes to quench QD PL, there are examples that use electron accepting molecules, such as quinones, to monitor enzyme activity 199,200 and intracellular pH, 183 or bipyridinium, to monitor receptor-substrate interactions. 180 Initially, Yildiz et al electrostatically adsorbed a bipyridinium dye to the surface of QDs and found that a macrocyclic receptor, cucurbit [7]uril, could disrupt the CT quenching interaction through competitive host-guest interactions.…”
Section: Bioanalysis and Bioimaging With Quantum Dotsmentioning
confidence: 99%
See 1 more Smart Citation
“…9A). 11 In addition to sensing configurations that use hole accepting metal complexes to quench QD PL, there are examples that use electron accepting molecules, such as quinones, to monitor enzyme activity 199,200 and intracellular pH, 183 or bipyridinium, to monitor receptor-substrate interactions. 180 Initially, Yildiz et al electrostatically adsorbed a bipyridinium dye to the surface of QDs and found that a macrocyclic receptor, cucurbit [7]uril, could disrupt the CT quenching interaction through competitive host-guest interactions.…”
Section: Bioanalysis and Bioimaging With Quantum Dotsmentioning
confidence: 99%
“…183,199,200,202 Freeman et al functionalized QD 620 with peptides containing a phosphotyrosine residue (8 6 2 per QD) to monitor the activity of alkaline phosphatase (ALP). 200 Initially, QDs were unquenched and retained their PL upon hydrolysis of the phosophotyrosine residue by ALP. However, in the presence of a reporter enzyme, tyrosinase, the resultant tyrosine residue is oxidized to a dopaquinone residue that quenched QD PL via CT. Quantification of ALP was demonstrated over the range 0.05-0.5 units in the presence of 25 units of tyrosinase.…”
Section: Bioanalysis and Bioimaging With Quantum Dotsmentioning
confidence: 99%
“…GSH capped QDs were synthesized based on previously reported procedures [27]. The resulting QDs were dissolved in 200 L borate buffer (pH 7.4, 10 mM).…”
Section: Preparation Of Gsh Capped Qdsmentioning
confidence: 99%
“…Several fluorescence probes generated from conjugated polyelectrolyte [11][12][13], quantum dots [14][15][16], noble metal nanoclusters [17,18] and organic fluorophores [19][20][21] have been reported for the detection of ALP activities. Despite many achievements from the above-mentioned successful studies, all of them work under one-photon excitation, which requires a rather short excitation wavelength (usually <500 nm).…”
Section: Introductionmentioning
confidence: 99%